Drug Counselors' Attitudes Toward Nonpharmacologic Treatments for Chronic Pain. Issue 1 (February 2016) - Oberleitner, Lindsay M.; Beitel, Mark; Schottenfeld, Richard S.; Kerns, Robert D.; Doucette, Christopher; Napoleone, Renee; Liong, Christopher; Barry, Declan T.
Abstract : Objectives: To examine methadone counselors' attitudes toward individual and group-based nonpharmacologic treatments for chronic pain. Methods: Thirty methadone drug counselors were interviewed about their attitudes toward pain interventions and completed a survey on the perceived efficacy of and willingness to refer patients to nonpharmacologic pain treatments. Results: Counselors reported favorable attitudes toward interventions commonly found in interdisciplinary pain management, particularly, conventional psychological approaches. On average, counselors rated cognitive-behavioral therapy (individual or group) as the treatment with the highest perceived efficacy and the one to which they were most willing to refer patients with pain. In contrast, on average, counselors rated the use of herbal medicine, aromatherapy, and magnets among the lowest in perceived efficacy and in willingness to refer patients with pain. Generally, higher perceived efficacy was associated with higher referral willingness, and scores on both dimensions were comparable across individual and group interventions. Conclusions: Findings indicate that methadone drug counselors perceive several nonpharmacologic evidence-based pain treatments as efficacious for methadone-maintained patients with chronic pain and counselors would be willing to refer their patients to these therapies if they were available. If some of these nonpharmacologic interventions were shown to be effective in methadone maintenance treatment, they have the potential to address, at least in part, the routine undertreatment of pain in this vulnerable patient population.